Notary Role In Making Cooperation Deed Based On Act No. 25 Of 1992 On Cooperatives In The Kudus District - Davit Hari Sanjaya; Wilmar Ibni Rusydan; Achmad Sulchan (Jurnal Akta, 2019)
The purpose of this study are to: 1) To determine and analyze the role of the Notary In Making Cooperative Deed Based on Act No.25 of 1992 on Cooperatives in Kudus District, 2) To determine the barriers and solutions with other legal regulations. The data used in this research is the primary data secondary data to support the assessment, which is then analyzed by socio-juridical.Based on data analysis concluded that: 1) The results of this study indicate Notary Role In Making Deed of Cooperative Members ie till Endorsement Process Deed by the competent authority, the Minister, the Act is used in the manufacture Cooperation Deed is the Act No.25 1992. the role of the Notary in making Cooperation Deed stipulated in the Decree of Minister Number 98 / KEP / M.UKM / IX / 2004, in addition to the Basic Law Firm ratification process Cooperatives, Government Regulation No. 4 of 1994 on the Terms and Procedure for Approval of Amendment to Articles of Incorporation Deed Basics Cooperative, and Regulation No. 01 Of 2006 that is on Implementation Guidelines for the Establishment, Approval of establishment and amendments of the Cooperative. 2) There are several notaries who are new that have not signed up to become a Notary Deed Official Land should Notary new one immediately enroll into NPAK, in the manufacture of Cooperation Deed Notary still ask for services to prospective Cooperative who can not afford, while at Law Notary is not mandatory enlist the services with the provisions of the Cooperative it was completely incapable and must have a letter from the Village, the reason besides pembuatanya complicated and lengthy the Notary still ask for services but the cost at most minimal, a notary is excluded by the founder and the Department of Cooperatives in meetings of formation, so that each holding Formation meeting cooperative cooperative Division move itself without the presence of a Notary, the Notary should be invited in the meeting included joint founder of the cooperative Formation, in the execution of the Deed of cooperatives, making the slowest period of 3 months and the fastest 7 working days.Keywords: Notary Role; Deed Making; Cooperative